The Terrorist Age‐Crime Curve: An Analysis of American Islamist Terrorist Offenders and Age‐Specific Propensity for Participation in Violent and Nonviolent Incidents. (26th February 2016) - Klausen, Jytte; Morrill, Tyler; Libretti, Rosanne
Abstract : Objective: This study examines the age‐crime relationship among terrorist offenders. Method: This study relies on a data set of over 600 American terrorism offenders inspired by one of three Islamist groups: Hamas, Hezbollah, or Al Qaeda. Results: We find that the pattern of violent Islamist crime in the United States departs from the standard age‐crime curve in significant ways. Violent action among terrorist offenders peaks at a later age and occurs across a broader age range than is the case for ordinary violent crimes.